Increased Cerebellar-Default-Mode-Network Connectivity in Drug-Naive Major Depressive Disorder at Rest. Issue 9 (March 2015) - Guo, Wenbin; Liu, Feng; Liu, Jianrong; Yu, Miaoyu; Zhang, Zhikun; Liu, Guiying; Xiao, Changqing; Zhao, Jingping
Abstract : Abstract: The default-mode network (DMN) has been implicated in the neurobiology of major depressive disorder (MDD), and the cerebellum is suggested to be involved in high-order cognitive network such as the DMN. However, the specific contribution of the cerebellum to the DMN alterations remains equivocal. This study was conducted to examine the cerebellar-DMN connectivity in drug-naive MDD directly by using the cerebellum Crus I as seeds. Forty-four drug-naive MDD patients and 44 healthy controls participated in the resting-state scan. Functional connectivity (FC) was applied to analyze the images. Significantly increased FCs were observed between the right Crus I and the right inferior frontal cortex (orbital part)/superior temporal pole, bilateral MPFC (orbital part), and left middle temporal gyrus in the patients compared with the controls. There was a significantly positive correlation between the z values of the right Crus I–bilateral MPFC (orbital part) connectivity and the scores of Automatic Thoughts Questionnaire in the patients ( r = 0.329, P = 0.029). The findings reveal that depressed patients have increased cerebellar-DMN connectivity with clinical significance, and thus highlight the contribution of the cerebellum to the DMN alterations in neurobiology of MDD.